2022
DOI: 10.1021/acsaem.2c01816
|View full text |Cite
|
Sign up to set email alerts
|

(3-Aminopropyl)triethoxysilane as an Electrolyte Additive for Enhancing the Thermal Stability of Silicon Anode in Lithium-Ion Batteries

Abstract: Silicon (Si), which can give a high capacity, is a potential next-generation anode material for lithium-ion batteries (LIBs), though there is a growing concern over the safety of Si-based batteries with higher energy density, where the reaction between the electrolytes and the charged electrodes can cause thermal issues. In our study, we developed an electrolyte additive which effectively improves the thermal stability of Si electrodes. Specifically, addition of 5 wt % (3-aminopropyl)­triethoxysilane (APTES) i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 64 publications
0
8
0
Order By: Relevance
“…By comparison, it can be observed that the 5% weight loss temperature of the PI polymer is about 100 °C higher than that of PI-COOH, and the gap is narrowed at 10% weight loss. Although the introduction of the −COOH group lowers the thermal decomposition temperature, the thermal properties of the PI-COOH still satisfy the requirement of thermal decomposition temperature . Appropriate electrolyte adsorption of the electrode can boost the diffusion of Li + to Si particles so as to achieve the high-rate capability and high-power capacity of lithium-ion battery .…”
Section: Results and Discussmentioning
confidence: 99%
“…By comparison, it can be observed that the 5% weight loss temperature of the PI polymer is about 100 °C higher than that of PI-COOH, and the gap is narrowed at 10% weight loss. Although the introduction of the −COOH group lowers the thermal decomposition temperature, the thermal properties of the PI-COOH still satisfy the requirement of thermal decomposition temperature . Appropriate electrolyte adsorption of the electrode can boost the diffusion of Li + to Si particles so as to achieve the high-rate capability and high-power capacity of lithium-ion battery .…”
Section: Results and Discussmentioning
confidence: 99%
“…Tan et al . found that (3‐aminopropyl)triethoxysilane (APTES) additives can act as a PF 5 /HF scavenger and stabilize the electrolyte at a high temperature [129] . Besides, the polymerization of APTES formed a protective layer on the anode, thereby improving the thermal stability of the silicon anode, as shown in Figure 4e.…”
Section: Mitigation Strategies For Thermal Runawaymentioning
confidence: 99%
“…Tan et al found that (3-aminopropyl)triethoxysilane (APTES) additives can act as a PF 5 /HF scavenger and stabilize the electrolyte at a high temperature. [129] Besides, the polymerization of APTES formed a protective layer on the anode, thereby improving the thermal stability of the silicon anode, as shown in Figure 4e. Other types of interphase additives can also form rigid and tough SEI on the silicon anode, such as trifluoropropylene carbonate, [130] LiNO 3 , [131] pentafluorophenyl isocyanate.…”
Section: Interphase Additivesmentioning
confidence: 99%
See 2 more Smart Citations